Pete the cat five little pumpkins - Dean, James 1957- (New York, NY HarperCpllins Children's Books, an imprint of HarperCollinsPublishers, 2015)
Join Pete the Cat as he rocks out to this cool adaption of the classic Halloween song "Five little pumpkins."
Ages 4-8.
Keywords: Picture books for children; Cats -- Juvenile fiction; Children's songs, English -- United States -- Texts; Songs; Cats -- Songs and music